Making the Link: Agricultural Research and Technology Transfer in Developing Countries - Kaimowitz, David (International Service for National Agricultural Research, 1990)
New technology generated by scientists and disseminated to farmers through the process known as technology transfer drives agricultural development world-wide. Building effective links between scientists, technology transfer workers, and farmers is vital to this process and is one of the most widely debated issues in agriculture today. In this volume, produced under the sponsorship of the International Service for National Agricultural Research (ISNAR) based in the Netherlands, eleven well-known specialists offer a multidisciplinary evaluation, stimulating new insight and giving new direction to solutions for this complex problem. Agricultural scientists and technology transfer workers, managers of agricultural research and extension organizations, policy makers concerned with public ad ministration, and scholars interested in these issues will find special value in this fresh approach to agriculture in the developing world.